Hallowed ground and hollow victories: reckoning with Civil War history and memory through expanded interpretation at Manassas National Battlefield Park - Henry, Cait Michelle (Kansas State University, 2024)
This dissertation is a culmination of both empirical and positional chapters that aim to create positive, outcome-based discussions surrounding how Civil War heritage and history is interpreted at National Park Service (NPS) historic sites like Manassas National Battlefield Park (MANA). As such, what follows is a critical analysis of the intersection between collective memory and history, along with what role NPS onsite interpreters play in shaping current social values and morals. Chapter one provides an overview of the literatures necessary to holistically understand the study problem and purpose. Research into collective memory and Southern heritage, the history of heritage preservation and interpretation within the National Park Service, and the histories of the Civil War battles that occurred at the study site are synthesized. Then, the chapter delves into the history currently interpreted at MANA before describing the structure of the dissertation and its main research purposes of illuminating disparities between the interpretive legacy of the site and what historic records and public histories are available that can be integrated into expanded interpretation programs and exhibits at the park. Chapter two details an empirical exploratory study that utilized an offsite, online panel sample survey to gain insight into both visitor and non-visitor perceptions of welcomeness and belonging, their moral foundations, and their preferences for interpretive themes that were co-created with park staff to be feasible to create currently or in the future. Results suggest that non-visitors perceive themselves to be less welcome at MANA than visitors, although there were no significant differences within perceived constraints to visitation. Results also indicated that highlighting interpretive themes like the Battles of Manassas and Slavery as a Cause of the Civil War may attract people who have higher scores on the Harm and Fairness moral foundation spectrums, who were also found to be more likely to visit the park. Chapter three is a position paper wherein the author argues that prior NPS interpretive themes surrounding historic battlefields are no longer relevant for the current American melting-pot constituency. With this in mind, I posit that the NPS is an organization that is partially dedicated to preserving, transmitting, and stabilizing collective memories of individual units that can be combined into a master narrative of episodic historic events of which United States citizens can integrate values, morals, or symbols into individual personal identities after visiting one or more NPS units. Moreover, emphasizing narratives of heroic white masculinity as part of the American Identity can be linked to detrimental effects of predominantly white or white passing men who enact violence on other citizens perceived as threats. When utilizing a framework of repeated trauma, these narratives of heroic white masculinity at Civil War battlefields are instead traumatic experiences that are transmitted to the public without awakening to the root trauma, which is truly reckoning with the causes and consequences of the Civil War—both historic fact and collective memory. The final chapter is a reflection on the dissertation process, the project’s previous iterations, and the limitations of both the work and the author. It also utilizes a critical lens, but does so within the psychological realm of meaning making, meaningful work, and self-transcendence. While this project was initially spatially bound to a single NPS unit, the author proposes that the findings and arguments within this dissertation can be applied more broadly and within interdisciplinary avenues to better understand the intersection of protected areas, cultural landscapes, American Identity, and geotrauma through studying sites of violence.
Keywords: National Park Service; Civil War; Manassas National Battlefield; Confederate heritage; Interpretation; Welcomeness and belonging